Unforgettable : an It girl novel - Von Ziegesar, Cecily (New York : Little, Brown, 2007)
Callie Vernon has never shared much with Jenny Humphrey, her younger, rosy-cheeked roommate at elite Waverly Academy, but when Jenny steals Callie's long-term boyfriend, Easy Walsh, Callie feels little guilt about kissing him behind Jenny's back.
Ages 15 and up.
Keywords: Boarding schools -- Fiction; Teenage girls -- Fiction; Interpersonal relations -- Fiction; Wealth -- Fiction; Conduct of life -- Fiction; Dating (Social customs) -- Fiction; Conduct of life -- Fiction; Interpersonal relations -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; New York (State) -- Fiction; New York (State) -- Fiction